Cambridge reading adventures: skyscrapers :3 explorers - Oxlade, Chris; Laszlo Veres (UK Cambridge university press, 2017)
Discover how skyscrapers are built and find out more about some of the world's most spectacular skyscrapers, including the Burj Khalifa and Petronas Twin Towers. Books in the Explorers strand are for learners who are reading a wide range of fiction and non-fiction with a good degree of accuracy and reasonable reading pace. Fiction books like this one contain chapters that allow for sustained reading over a period of time. Readers at this strand will be able to discuss their reading preferences and read critically considering the author's effectiveness. Contains teaching support including learning outcomes, curriculum links and follow-up activities.